Multiscale models of habitat use by mule deer in winter. Issue 6 (14th May 2018) - Coe, Priscilla K.; Clark, Darren A.; Nielson, Ryan M.; Gregory, Sara C.; Cupples, Jacqueline B.; Hedrick, Mary Jo; Johnson, Bruce K.; Jackson, Dewaine H.
ABSTRACT: Mule deer ( Odocoileus hemionus hemionus ) populations have experienced widespread declines in much of western North America and alteration or loss of habitat could be contributing to these declines. Consequently, understanding habitat features that are important to mule deer is necessary for effective management of the species and their habitat. From 2005–2012 we radio‐marked 452 mule deer with global positioning system collars across 9 distinct winter ranges to evaluate winter habitat use along the east slope of the Cascade Range in south‐central Oregon, USA. Using data from 357 mule deer across 9 analysis areas, we developed regional habitat use models for mule deer on winter range at 3 spatio‐temporal scales: herd range based on 100% minimum convex polygons around deer locations, home range based on 90% kernel density estimates of deer locations, and foraging range based on locations obtained within 2 hours of sunrise or sunset within the boundaries of the home range scale. We assessed habitat use of mule deer using a generalized linear model with a negative‐binomial link function. We validated our models with locations from an independent dataset of 95 deer that wintered within 8 of our analysis areas. Model validation indicated that regional models for all spatio‐temporal scales predicted probability of use moderately to very well. At all spatio‐temporal scales, predicted use by mule deer was greater in areas with forest canopy cover. These findings call into question large‐scale removal of western juniper ( Juniperus occidentalis ) in Oregon and other portions of western United States to enhance habitat for sagebrush‐dependent wildlife species. Across all spatio‐temporal scales, we documented increased probability of use of areas farther from roads open to motorized vehicle use by mule deer, highlighting the importance of limiting motorized vehicle use and access on mule deer winter range. We also documented increased use of areas with lower snow depth and on moderate slopes by mule deer. Our models can be used in land management planning to spatially predict mule deer distribution and probability of use under alternative management scenarios that affect forest canopy cover or motorized vehicle use on roads while accounting for other physical features of the landscape. Additionally, our models can be used to develop juniper removal projects to mitigate effects on mule deer winter range habitat while benefiting other wildlife. © 2018 The Wildlife Society. Abstract : Our analysis of habitat use of mule deer on winter range indicated mule deer used areas with increased forest cover and farther from roads open to motorized vehicle use. Our findings suggest habitat manipulations that reduce forest cover could be detrimental to mule deer and seasonal or permanent closure of roads open to motorized vehicle use on winter range could benefit mule deer.